Exploring the sense of belonging and the notion of home in Margaret Atwood’s Cat’s Eye - Ahmad Jafni, Nur Fatin Syuhada; Wan Yahya, Wan Roselezam (SciPress Ltd, 2014)
Human beings need to associate and mingle with their surroundings, be they the family, neighbours, colleagues, nature or a place, in order to feel attached and belonging to a particular society and its environment. This article explores the concept of a sense of belonging in Margaret Atwood’s novel Cat’s Eye (1988). The story is about the protagonist, Elaine, revisiting her childhood memories, where she learned about friendship, longing and betrayal. Although she was being bullied by her own best friends, Elaine remained with them as she feared being alienated. Despite the many years spent outside Toronto and away from her sad childhood memories, Elaine still felt that her hometown was her real home. The notions of belongingness used in this analysis are aided by Abraham Maslow’s Hierarchy of Needs and William Glasser’s Choice Theory. Elaine’s strong attachment to her hometown and her childhood memories is due to the human needs for love and belonging and in an attempt to evade alienation and loneliness. Parallel to what Maslow defines as a sense of belonging, humans on a very basic level long for belonging, respect and love, and Elaine’s actions are seen as a desperate attempt to get through her days in the way that Glasser outlines in Choice Theory – the need for love and belonging is closely linked to the need for survival.